2010
DOI: 10.1021/ma101013c
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Functional Monomer Dimerization in the Molecular Imprinting Process

Abstract: H NMR spectra were recorded on a Varian 300 MHz NMR at ambient temperature. Chemical shifts (ppm) were referenced to tetramethylsilane or residual protonated solvent. UV measurements were made using a Jasco V-530 spectrometer. Solvents were purchased from Sigma-Aldrich, Fisher, VWR, and were purified and dried by passing through a PURE SOLV® solvent purification system (Innovative Technology). Deuterated solvents were purchased from Cambridge Isotope Laboratories. All other reagents were purchased from Sigma-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 67 publications
(145 reference statements)
0
55
0
1
Order By: Relevance
“…Afterwards, Zhang et al 41 explained why MAA is such a versatile monomer for molecular imprinting, and revealed that the dimerization of MAA modestly enhanced the imprinting effect, as illustrated in Fig. 3.…”
Section: Functional Monomersmentioning
confidence: 99%
“…Afterwards, Zhang et al 41 explained why MAA is such a versatile monomer for molecular imprinting, and revealed that the dimerization of MAA modestly enhanced the imprinting effect, as illustrated in Fig. 3.…”
Section: Functional Monomersmentioning
confidence: 99%
“…NMR titration, a relatively common method in host-guest chemistry, was used to determine binding constants where host and guest are mixed in different ratios and the NMR spectrum of the mixture is measured. NMR titration is often used to understand complexation phenomena in macrocycle chemistry 7,8,9 , molecular imprinting 10,11 and receptors 12,13 . Due to fast-exchange correlation the NMR signals of the complexes and the initial compounds do not appear separately but as their average.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of molecularly imprinted polymers (MIP) typically involves three steps: first, a monomer-template [M-T] complex is formed via self-assembly; next, the M-T complex is polymerized with an excess of cross-linker to form a rigid polymer; finally, the template is removed, leaving behind binding cavities which are complementary in shape and functional group to the template [2]. The vast majority of MIP is based on the use of organic acrylate-type polymers: a standard procedure using a methacrylate monomer, with a nearly optimal ratio to the template molecule and crosslinker, is described in numerous works [2][3][4][5][6][7][8]. The broad applicability of methacrylic acid (MAA) as a functional monomer in MIP production is related to the fact that the carboxylic acid group serves well as a hydrogen bond and proton donor as well as a hydrogen bond acceptor [9].…”
Section: Introductionmentioning
confidence: 99%